Exchange of short-chain oxygenated volatile organic compounds (VOCs) between plants and the atmosphere: A compilation of field and laboratory studies - Kesselmeier, J (Journal of Atmospheric Chemistry, 2001)
Field and laboratory investigations of the exchange of the short-chain organic acids – formic acid and acetic acid – as well as their homologous aldehydes are discussed. Both acids are substantially released from several plant species. Emission measurements under ﬁeld conditions are compiled to give an overview of three years of measurements. Emission rates from several tree species were found in the range between zero and 60 nmoles m−2 min−1 for acetic acid and between zero and 90 nmoles m−2 min−1 for formic acid though also a deposition has been observed to orange trees. Investigations under laboratory conditions showed an order of magnitude lower emission rates with signiﬁcant differences under light and dark conditions, and a deposition was observed under certain conditions. Hence, low emission rates or even a bi-directional exchange, emission as well as deposition have to be taken into account. Further differences between ﬁeld and laboratory studies are discussed considering age of trees, stress effects and a potential production of acids by photochemical conversion of precursors inside enclosures during sampling. Field data on the exchange of formand acetaldehyde show a complex behavior. We found emission as well as uptake. The bi-directional exchange is signiﬁcantly triggered by the ambient mixing ratios of both aldehyde species and exhibits a compensation point. Further studies are needed for generalization of the exchange of these and potentially also for other compounds
Keywords: Acetaldehyde; acetic acid; biogenic deposition; Biogenic emission; carbonyls; compensation point; Formaldehyde; formic acid; organic acids; Volatile Organic Compounds

An overview of the Castelporziano experiments - Seufert, G; Bartzis, J; Bomboi, T; Ciccioli, P; Cieslik, S; Dlugi, R; Foster, P; Hewitt, C N; Kesselmeier, J; Kotzias, D; Lenz, R; Manes, F; et al. (Atmospheric Environment, 1997)
This paper reviews the major outcomes of the measuring campaigns performed at the Castelporziano nature preserve near Rome, Italy, by 14 European laboratories as part of the BEMA (Biogenic Emissions in the Mediterranean Area)-project. Six campaigns of 1–4 weeks duration were carried out in different seasons of the years 1993–1994 at semi-continuously running test plots in the nature reserve, representing common Mediterranean vegetation types. The aim was to characterise, at the different test plots, the atmospheric chemical and meteorological situations, the plant biomass and physiology, the type, amount and controls of emissions from different plants by means of branch enclosures, and the BVOC emission fluxes from different ecosystems, by scaling up enclosure data from individual sources, and by measuring fluxes directly by use of micrometeorological methods. An important focus during the initial phase of the five year BEMA-project was the harmonisation and improvement of the analytical, physiological and micrometeorological methods used, and the development and testing of new methods for measuring BVOC fluxes.
Keywords: air chemistry; Biogenic emission; ecophysiology; Mediterranean area; micrometeorology; Vegetation

EMISSION OF MONOTERPENES AND ISOPRENE FROM A MEDITERRANEAN OAK SPECIES QUERCUS ILEX L. MEASURED WITHIN THE BEMA (BIOGENIC EMISSIONS IN THE MEDITERRANEAN AREA) PROJECT EMISSIONS IN THE M E D I T E - Kesselmeier, J; Fer, L S C H; Ciccioli, P; Brancaleoni, E; Cecinato, A; Frattoni, M; Foster, I P; Jacob, V; Denis, J; Fugit, J L; Dutaur, L; Torres, L; et al. (Atmospheric Environment, 1996)
We report on some results of our studies of monoterpene and isoprene emissions and the physiological activities of an oak species (Quercus ilex L.) under the Mediterranean climatic conditions found at Castel Porziano (Rome) in June 1993. The oak species Quercus ilex L. was found to emit mainly monoterpenes in high amounts. Isoprene emissions were negligible. Diel cycles of monoterpene emissions showed correlation with light and the diel behaviour of photosynthetic CO2 assimilation, transpiration and stomatal corductance. Temperature dependence seemed to be of minor importance.
Keywords: Biogenic emission; isoprene; light; Monoterpenes; non-methane hydrocarbons; oak; Plant physiology; VOC